Analisis Faktor-Faktor yang Mempengaruhi Penerapan Standar Akuntansi Keuangan dalam Penyusunan Laporan Keuangan - Niken Lestari, Onnika; Arnova, Iwin; Herawati, Helmi (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2025)
This study aims to determine whether there is an influence of human resource competence, information technology, and management commitment on the preparation of financial reports. The type of data in this study is quantitative research, with the data source in this study being primary data obtained directly from respondents through distributing questionnaires to employees. The population in this study were all employees working at PT Palma Mas Sejati, totaling 76 people with various fields of duties and responsibilities. The sample taken by researchers in this study was 35 employees. The independent variable in this study is the preparation of financial reports, the dependent variable is human resource competence, information technology, and management commitment. The results of the study show that human resource competence, information technology and management commitment have an effect on the preparation of financial reports of PT Palma Mas Sejati, Talang Empat Village, Central Bengkulu Regency. This can be shown from the significant value below 0.05 (5%). Human resource competency, information technology, and management commitment simultaneously (together) influence the preparation of financial reports of PT Palma Mas Sejati, Talang Empat Village, Central Bengkulu Regency. This is indicated by the value below 0.05 (5%). The results of this study are expected to be input for companies in improving the quality of financial report preparation by strengthening human resource competencies, more optimal use of information technology, and increasing management commitment in implementing Financial Accounting Standards.